2013
DOI: 10.1007/s10803-013-1775-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Manifestations of Anxiety in Children with Autism Spectrum Disorders

Abstract: This study explores the manifestation and measurement of anxiety symptoms in 415 children with ASDs on a 20-item, parent-rated, DSM-IV referenced anxiety scale. In both high and low-functioning children (IQ above vs below 70), commonly endorsed items assessed restlessness, tension and sleep difficulties. Items requiring verbal expression of worry by the child were rarely endorsed. Higher anxiety was associated with functional language, IQ above 70 and higher scores on several other behavioral measures. Four un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
107
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(121 citation statements)
references
References 30 publications
12
107
1
1
Order By: Relevance
“…In a review of 40 studies, White, Oswald, Ollendick, and Scahill (2009) report that between 11 and 84% of children with ASD also exhibit anxiety symptoms and that 'anxiety may worsen during adolescence ' (p. 216). High levels of anxiety symptoms are identified in relation to: social anxiety; generalised anxiety, separation anxiety; specific phobias and obsessive-compulsive disorder (Gillott, Furniss, & Walyerm, 2001;Hallett et al, 2013).…”
Section: Asd and Anxietymentioning
confidence: 99%
“…In a review of 40 studies, White, Oswald, Ollendick, and Scahill (2009) report that between 11 and 84% of children with ASD also exhibit anxiety symptoms and that 'anxiety may worsen during adolescence ' (p. 216). High levels of anxiety symptoms are identified in relation to: social anxiety; generalised anxiety, separation anxiety; specific phobias and obsessive-compulsive disorder (Gillott, Furniss, & Walyerm, 2001;Hallett et al, 2013).…”
Section: Asd and Anxietymentioning
confidence: 99%
“…The validity and reliability of standard anxiety inventories among children with ASD are under active investigation (Wood and Gadow, 2010;Van Steensel et al, 2012;Hallett et al, 2013). The parent report version of the Screen for Child Anxiety Related Emotional Disorders (SCARED; Birmaher et al, 1997) was selected for two reasons.…”
Section: Participantsmentioning
confidence: 99%
“…Prevalence estimates of anxiety disorders in ASD vary widely (Simonoff, 2005), with more recent studies indicating rates in excess of 40% (Leyfer et al, 2006;Sukhodolsky et al, 2008). It appears likely that most if not all anxiety disorders occur at an elevated rate in ASD (Sukhodolsky et al, 2008;Hallett et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…; DSM-IV) referenced instrument designed to screen for child psychiatric disorders (Gadow and Sprafkin, 2002). In a sample of 415 children (aged 4-17 years) with ASD enrolled in one of four multisite trials, Hallett et al (2013) showed that on the CASI Anxiety scale, some children were low on anxiety, others were rated in the mild-to-moderate range, and still others had scores suggesting high anxiety. However, items beginning with "worries" or "complains" were seldom endorsed in this sample, suggesting that items reliant on language may not be useful in children with ASD.…”
mentioning
confidence: 99%